Cultural adaptation of a UK evidence-based problem-solving intervention to support Polish prisoners at risk of suicidal behaviour: a cross-sectional survey using an Ecological Validity Model - Amanda E Perry; Maja Zawadzka; Piotr Lapinski; Keeley Moore; Jaroslaw Rychlik; Beata Nowak (BMJ Open, 2023)
Objective To complete a cultural adaptation of a UK evidence-based problem-solving intervention to support Polish prisoners at risk of suicidal behaviour.Design A cross-sectional survey participatory design using an Ecological Validity Model.Setting The study was a collaboration between: the Academy of Justice, in Warsaw, the University of Lodz, two Polish prisons (ZK Raciborz and ZK Klodzko) and the University of York (UK).Methods The adaptation process included an examination of the use of language, metaphors and content (ie, culturally appropriate and syntonic language), the changing of case study scenarios (relevance and acceptability) and maintenance of the theoretical underpinning of the problem-solving model (intervention comprehensibility and completeness). Four stages used: (1) a targeted demonstration for Polish prison staff, (2) a wider audit of the skills with Polish prison staff and students, (3) forward and back-translation of the adapted package, and (4) two iterative consultations with participants from stages (1) and (2) and prison officers from two Polish prisons.Participants Self-selecting volunteer participants included: targeted prison staff (n=10), prison staff from the wider Polish penitentiary system (n=39), students from the University of Lodz (n=28) and prison officers from two Polish prisons (n=12).Main outcomes and measures Acceptability and feasibility of the training package, reported in a series of knowledge user surveys.Results The recognised benefits of using the skills within the training package included: enhancing communication, reflective development, collaborative working, changing behaviour, empowering decision-making, relevance to crisis management situations and use of open-ended questions. The skills were endorsed to be used as part of future penitentiary training for prison officers in Poland.Conclusions The skills had widespread appeal for use across the Polish penitentiary system. The materials were deemed relevant while adhering to the comprehensibility of the intervention. Further evaluation of the intervention should be explored using a randomised controlled trial design.